Effectiveness of percutaneous lumbar foraminoplasty in patients with lumbar foraminal spinal stenosis accompanying redundant nerve root syndrome: A retrospective observational study - Jeong, Ki-Soon (Medicine (Baltimore), 2020)
The clinical outcomes of redundant nerve root syndrome (RNRS) in patients with lumbar foraminal spinal stenosis (LFSS) are currently unknown. The purpose of this study was to evaluate the postprocedural outcomes of RNRS in LFSS after percutaneous lumbar foraminoplasty (PLF) and identify the factors associated with RNRS by comparative analysis between patients with and without RNRS. Patients with LFSS who underwent PLF were retrospectively analyzed. RNRS is defined as the presence of thick, elongated, and tortuous structures in the cauda equine associated with lumbar spinal stenosis. Based on the sagittal or transverse magnetic resonance imaging scans obtained before the PLF, the patients were stratified into 2 groups. Comparative analysis was performed between patients with RNRS (group R) and those without RNRS (group C). From March 2016 to January 2019, 8 of the 21 (38.1%) patients undergoing PLF showed signs of RNRS on magnetic resonance imaging images. PLF showed a tendency for less therapeutic effect with respect to changes in pain intensity in group R as compared to group C, but there were no statistically significant differences between the 2 groups. RNRS correlated with the cross-sectional area (CSA) of the dural sac and LFSS grade (P < .05). The CSA of the dural sac was smaller and the grade of LFSS was higher in group R than in group C. RNRS is commonly associated with lumbar spinal stenosis and could affect the treatment outcomes. Clinical outcomes in group R were not statistically different from those in group C, although group R showed slightly worse outcomes. The independent factors associated with RNRS were CSA of the dural sac and the LFSS grade.